2021
DOI: 10.1093/ehjacc/zuaa035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and shock severity on short-term survival in patients with cardiogenic shock

Abstract: Aims Cardiogenic shock (CS) is associated with poor outcomes in older patients, but it remains unclear if this is due to higher shock severity. We sought to determine the associations between age and shock severity on mortality among patients with CS. Methods and results Patients with a diagnosis of CS from Mayo Clinic (2007–15) and University Clinic Hamburg (2009–17) were subdivided by age. Shock severity was graded using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 35 publications
3
70
1
Order By: Relevance
“…Moreover, the majority of published analyses have focused on CS from AMI. A recent 2 center study reported congruent findings of graded relationship between older age and lower survival in CS that was additive to the level of shock severity (16). Although CS was identified using a diagnosis code and a large percentage of patients were in early, stage B shock, our findings strengthen their observation that age and increasing shock severity are associated with worse outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the majority of published analyses have focused on CS from AMI. A recent 2 center study reported congruent findings of graded relationship between older age and lower survival in CS that was additive to the level of shock severity (16). Although CS was identified using a diagnosis code and a large percentage of patients were in early, stage B shock, our findings strengthen their observation that age and increasing shock severity are associated with worse outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…With the introduction of the Society for Cardiovascular Angiography and Intervention (SCAI) CS stages, patients can now be classified consistently based on their severity of shock (14,15). Recent reports have noted that older patients with CS have lower short-term survival, despite similar shock severity (16). We sought to describe the relationships between age, SCAI stage, use of temporary MCS and mortality risk in patients with CS included in the Cardiogenic Shock Work Group (CSWG).…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Shock severity can be quantified using the Sequential Organ Failure Assessment (SOFA) cardiovascular subscore 5 , 7 , 8 or the Society for Cardiovascular Angiography and Interventions (SCAI) shock classification. 4 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 The SCAI shock classification was developed to grade the severity of CS, and unlike the SOFA cardiovascular subscore that was developed for sepsis, the SCAI shock classification incorporates the clinical trajectory and response to therapy. 7 , 16 The SCAI shock classification provides consistent mortality risk stratification in critically ill patients with underlying acute cardiac disease, including CICU patients and patients with CS.…”
mentioning
confidence: 99%
“…based on clinical criteria only). 14,18,19 Enrolment of patients with beginning CS is a sensible choice for randomised CS trials testing an intervention with a lower risk profile. As an example, the lactate criterion was not obligatory in IABP-SHOCK II, so that the application of the IABP was also tested in patients with beginning CS.…”
Section: Barriers To Trial Enrolmentmentioning
confidence: 99%